Existence and Uniqueness of Almost Periodic Solutions to Time Delay Differential Equations - Tuz, Münevver (Adiyaman University, 2024)
In this study, a time-delayed relational neural network model was examined. The existence of almost periodic solutions of time delay differential equation has been investigated, and its uniqueness and stability have been proven with the help of Lyapunov point theorem and differential inequality. Since the signal transmission process of the neural network changes periodically in the real world, many scientists have focused on this issue and the almost periodic function has gained great importance because it is more suitable for practical events. The results found are different from and complementary to the previous ones. © 2024, Adiyaman University. All rights reserved.
Zaman Gecikmeli Diferansiyel Denklemlerin Yaklaşık Periyodik Çözümlerinin Varlığı ve Tekliği
Keywords: Almost Periodic; Dynamic system; Globally exponentially stable; Lyapunov point theorem; Neural; Time-Varying Delays